Elevation of blood lipids in hepatocyte-specific fatty acid transport 4-deficient mice fed with high glucose diets - Döring, Stephan; Seeßle, Jessica; Gan-Schreier, Hongying; Javaheri Haghighi, Bahador; Cheng, Yuting; Tuma-Kellner, Sabine; Stremmel, Wolfgang; Chamulitrat, Walee (Molecular genetics and metabolism, 2019)
Fatty acid transport protein4 (FATP4) is upregulated in acquired and central obesity and its polymorphisms are associated with blood lipids and insulin resistance. Patients with FATP4 mutations and mice with global FATP4 deletion exhibit skin abnormalities characterized as ischthyosis prematurity syndrome (IPS). Cumulating data have shown that an absence of FATP4 increases the levels of cellular triglycerides (TG). However, FATP4 role and consequent lipid and TG metabolism in the hepatocyte is still elusive. Here, hepatocyte-specific FATP4 deficient (Fatp4L−/−) mice were generated. When fed with chow, these mutant mice displayed no phenotypes regarding blood lipids. However when fed low-fat/high-sugar (HS) or high-fat/high-sugar (HFS) for 12weeks, Fatp4L−/− mice showed a significant increase of plasma TG, free fatty acids and glycerol when compared with diet-fed control mice. Interestingly, Fatp4L−/− mice under HS diet had lower body and liver weights and they were not protected from HFS-induced body weight gain and hepatic steatosis. Male mutant mice were more sensitive to HFS diet than female mutant mice. Glucose intolerance was observed only in female Fatp4L−/− mice fed with HS diet. Lipidomics analyses revealed that hepatic phospholipids were not disturbed in mutant mice under both diets. Thus, hepatic FATP4 deletion rendered an increase of blood lipids including glycerol indicating a preferential fatty-acid channeling to TG pools that are specifically available for lipolysis. Our results imply a possible risk of hyperlipidemia as a result of abnormal metabolism in liver in IPS patients with FATP4 mutations who consume high-sugar diets.